Antagonism of SR 90107A/Org 31540-lnduced Bleeding by Protamine Sulfate in Rats and Mice - Bernat, A; Hoffmann, P; Herbert, J M (Thrombosis and Haemostasis, 1996)
The neutralization by protamine sulfate of bleeding enhancement induced by the potent anti-factor Xa pentasaccharide SR 90107A/Org 31540 and by heparin has been studied in rats and mice. Bleeding, as measured by transection of the tail of anaesthetised rats or mice, was increased following the administration of heparin and very high doses of SR 90107A/Org 31540. In rats, i.v. doses of 0.6 mg/kg heparin or 15 mg/kg SR 90107A/Org 31540 were required to enhance bleeding time to approximately the same extent (5- or 7-fold increase), whereas in mice a 13-fold increase in blood loss was observed with i.v. doses of 3 mg/kg heparin or 10 mg/kg SR 90107A/Org 31540. Protamine sulfate (10 mg/kg i.v.) reduced bleeding in rats and mice induced by both compounds. It also neutralized the anti-factor Xa activity as well as the antithrombotic activity of heparin as observed in venous thrombosis models in both species. However, protamine sulfate neither affected the anti-factor Xa activity nor the antithrombotic activity of SR 90107A/Org 31540 in rats and mice. The present results suggest that protamine sulfate may be regarded as a potential antidote to neutralize bleeding side-effects in cases of SR 90107A/Org 31540 overdosing.